Effects of mindfulness training on different components of impulsivity in borderline personality disorder: results from a pilot randomized study. Issue 1 (December 2016) - Soler, Joaquim; Elices, Matilde; Pascual, Juan; Martín-Blanco, Ana; Feliu-Soler, Albert; Carmona, Cristina; Portella, Maria
Abstract Background Impulsivity is considered a core characteristic of borderline personality disorder (BPD). Previous research on the effects of mindfulness training (MT) has shown that it might modify impulsivity-related aspects of BPD. Therefore, the aim of this study was to investigate the impact of MT on various facets of impulsivity in BPD patients. Methods Subjects with BPD diagnosis (n = 64) were randomly assigned to 10 weeks of MT (n = 32) or interpersonal effectiveness skills training (IE;n = 32). All participants were assessed pre- and post-intervention with a self-reported measure of impulsivity and five behavioral neuropsychological tasks to evaluate response inhibition, tolerance for delay rewards, and time perception. Results An interaction effect of time × group was only observed for some of the behavioral paradigms used. Participants in the MT group improved their ability to delay gratification and showed changes in time perception, consistent with a decrease in impulsivity. No differences were observed between treatments in terms of trait impulsivity and response inhibition. Conclusions Mindfulness training might improve some aspects of impulsivity but not others. Further study is warranted to better determine the effects of mindfulness training on the components of impulsivity. Trial registration ClinicalTrials.gov Identifier:NCT02397031 .